Nonlinear spillover effect of US monetary policy uncertainty on China’s systematic financial risks - Ouyang, Zhigang; Dou, Zhenjiang; Wei, Lei; Vasa, László (Journal of Business Economics and Management, 2022)
Monetary policy uncertainty (MPU) not only imposes a great impact on the systematic financial risks of a country but also generates a significant spillover effect on countries having close economic exchanges with the former under the background of global economic integration. With the daily return rates of 64 listed financial companies in China from February 2006 to September 2020 used as the samples, China’s systematic financial risks were measured in this research by using long-run marginal expected shortfall (LRMES). On this basis, an FAVAR model with time-varying parameters was constructed to empirically investigate the spillover effect of US MPU on China’s systematic financial risks and its main transmission channels. Results showed that within the sample period (February 2006 – September 2020), US MPU generated a significant positive spillover effect on China’s systematic financial risks, namely, China’s systematic financial risks would be aggravated if the level of US MPU was elevated. From different time intervals, the spillover level was particularly high during global financial crises and global COVID-19 pandemic, indicating that the spillover effect of MPU is nonlinear and closely related to global major sudden risk events. Through the further research, it is found that this effect is mainly transmitted through short-term capital flow, interest rate, and economic uncertainty-induced channels, among which the short-term capital flow is the most important.